2020
DOI: 10.1186/s12917-020-02376-6
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study to identify risk factors for adult-onset idiopathic megaoesophagus in Australian dogs, 2017–2018

Abstract: Background: Epidemiological investigations were carried out following detection of an outbreak of megaoesophagus in Victorian Police working dogs in early 2018 and an increase in the number of canine megaoesophagus cases reported by companion animal veterinarians in Eastern Australia starting in late 2017. VetCompass Australia data were used to quantify the incidence of canine megaoesophagus for the period January 2012 to February 2018 and a matched case-control study carried out to identify individual animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 15 publications
(14 reference statements)
0
3
0
8
Order By: Relevance
“…This case-control study showed that dogs with AIME were 437 (95% CI, 80 to 2,361) times as likely to have had a recent history of consuming Diet Y, compared with control dogs. 3 Furthermore, the subsequent decrease in the number of cases following the recall of Diet Y was additional evidence of the strong association between the consumption of Diet Y and the development of AIME.…”
Section: Australian Outbreak 2017 To 2018mentioning
confidence: 97%
See 2 more Smart Citations
“…This case-control study showed that dogs with AIME were 437 (95% CI, 80 to 2,361) times as likely to have had a recent history of consuming Diet Y, compared with control dogs. 3 Furthermore, the subsequent decrease in the number of cases following the recall of Diet Y was additional evidence of the strong association between the consumption of Diet Y and the development of AIME.…”
Section: Australian Outbreak 2017 To 2018mentioning
confidence: 97%
“…As with the Latvian outbreak, the UoM conducted a matched case-control study to identify risk factors for the development of AIME. 3 Also, the VetCompass Australia database was accessed to determine the incidence of AIME in an attempt to verify the supposition that AIME was associated with consumption of Diet Y. VetCompass Australia is a database of de-identified demographic and medical information from pet owner consultations and pet examinations from hundreds of veterinary clinics around Australia. 4 Veterinary researchers can mine the database to obtain a baseline of expected incidence and unexpected increased incidence, indicative of an outbreak, of various diseases.…”
Section: Australian Outbreak 2017 To 2018mentioning
confidence: 99%
See 1 more Smart Citation
“…Розширення стравоходу (мегаезофагус) -це патологія, яка частіше реєструється в собак і характеризується розширеним просвіту стравоходу [1]. Відповідно до літературних даних, розширення стравоходу може бути вродженим і набутим, або ідіопатичним і вторинним щодо інших захворювань [2].…”
Section: вступunclassified
“…Відповідно до літературних даних, розширення стравоходу може бути вродженим і набутим, або ідіопатичним і вторинним щодо інших захворювань [2]. Окремі автори зазначають, що набуте розширення стравоходу (мегаезофагус) у собак частіше є ідіопатичним (езофагоспазм) [1,3]. Причинами, що провокують набутий мегаезофагус, можуть бути системні міопатії, міастенія, гіпоадренокортицизм, дизавтономія, важкий езофагіт, отруєння Плюмбумом та аутоімунні захворювання [3,4].…”
Section: вступunclassified